Recipes for the Future : Previews from cultural quarantine - Gerlings, Beate; ter Haar, Lene; Houppermans, Valérie-Anne; Kaminski, Astrid ([S.l.] : Onomatopee, 2020)
Sixteen culture makers who are Zeitzeugen (contemporary witnesses) of the COVID-19 pandemic sketch how things can be different in the future. Their visions for the future came about as a reaction to the disruption of their plans for 2020, and have one thing in common: the ambition to change and to widen the limits of our imagination. The visions and recipes of these writers, academics, philosophers, singers, visual artists, theatre makers and designers working in the Netherlands and Germany, paint a heterogeneous picture. They develop through themes such as real utopias, sustainability, the new domesticity, and the role of cultural institutions in our society. This collection is flavoured with the food recipes that every maker has contributed. The menu ranges from eating earth to corona ice cream, from French toast to Mushrooms at the end of the world, and tastes like more. (provided by publisher)
boek